Phosphorus-solubilizing fungi promote the growth of Fritillaria taipaiensis P. Y. Li by regulating physiological and biochemical reactions and protecting enzyme system–related gene expression - Wang, Yueheng; Yuan, Lin; Wang, Yuhan; Lang, Jiaqi; Ye, Mingyan; Liu, Qingqiu; Ma, Qiang; Zhou, Nong (Frontiers in Genetics, 2025)
IntroductionFritillaria taipaiensis P. Y. Li is a plant used to treat respiratory diseases such as pneumonia, bronchitis, and influenza. Its wild resources have become increasingly scarce, and the demand for efficient artificial cultivation has increased significantly in recent years. Phosphorus-solubilizing fungi can promote the dissolution of insoluble phosphate complex, which benefits plant nutrition. Another strategy for efficiently cultivating traditional Chinese medicine plants is to combine the soil with phosphorus-solubilizing fungi to provide nutrients and other desired features. This study aimed to investigate the effects of different phosphorus-solubilizing fungi and their combinations on photosynthesis, physiological and biochemical characteristics, and expression of protective enzyme system–related genes, and to find a reference strain suitable for the artificial cultivation and industrial development of F. taipaiensis P. Y. Li. In this study, the phosphorus-solubilizing fungi isolated from the rhizosphere soil of F. taipaiensis P. Y. Li were applied to the cultivation of F. taipaiensis P. Y. Li for the first time.MethodsIn this study, seven treatment groups (S1-S7) and one control group were set up using indoor pots as follows: S1 (inoculation with Aspergillus tubingensis), S2 (inoculation with A. niger), S3 (inoculation with Aspergillus nigerfunigatus) and S4 (inoculation with A. tubingensis and A. niger), S5 (inoculation with A. tubingensis and A. nigerfunigatus), S6 (inoculation with A. niger and A. nigerfunigatus), S7 (inoculation with A. tubingensis, A. niger, and A. nigerfunigatus), and CK (control group). These strains were inoculated into pots containing F. taipaiensis P. Y. Li bulbs,and the effects of different phosphorus-solubilizing fungi and combinations on the photosynthetic characteristics, basic physiological and biochemical indicators, and differential gene expression of protective enzyme systems in F. taipaiensis P. Y. Li leaves were determined.ResultsMost growth indexes showed significant differences in the fungal treatment groups compared with the CK group (P < 0.05). The stem diameter and plant height in the S5 group were the highest, which were 58.23% and 62.49% higher than those in the CK group, respectively. The leaf area in the S7 group was the largest, which increased by 141.34% compared with that in the CK group. Except for intercellular CO2 concentration (Ci), the contents of photosynthetic pigments, photosynthetic parameters, and amounts of osmoregulatory substances increased to varying degrees in the fungal treatment groups (P < 0.05). Among these, the S5 group had the highest stomatal conductance index and soluble sugar and free proline contents, whereas S6 had the highest chlorophyll a and soluble protein contents. In addition, the malondialdehyde (MDA) content in all inoculation groups was lower than that in the CK group. The MDA content was the lowest in S7, about 44.83% of that in the CK group. The activities of peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT) were higher in all inoculation groups than those in the CK group; the changes in SOD and CAT activities were significant (P < 0.05). The expression levels of FtSOD, FtPOD, and FtCAT in the S5 group were the highest, which were 8.67, 7.65, and 6.08 times of those in the CK group, respectively.ConclusionVarious combinations of phosphorus-solubilizing fungi exhibit differential capacities to enhance plant growth indices (including leaf area, plant height, and stem diameter), promote the accumulation of photosynthetic pigments, regulate osmotic pressure, and elevate antioxidant activity. Notably, The three fungal combinations (S7) were prone to cause a certain degree of antagonism, leading to suboptimal performances in certain biochemical indicators, such as free proline and POD levels. Our study pointed out that the S5 group inoculated with A. tubingensis and A. niger had the best overall effect. These experimental results provided a theoretical basis for the selection and development of artificial cultivation of F. taipaiensis P. Y. Li.